Wear-resistant self-lubricating composite powder for slide plate, cladding layer and preparation method of wear-resistant self-lubricating composite powder

By laser cladding using copper-based wear-resistant self-lubricating composite powder on the surface of the sliding bed plate, an wear-resistant self-lubricating cladding layer is formed and subsequent processing is carried out, the problems of low energy conversion and low interface bonding strength in the laser cladding process of copper-based graphite self-lubricating composite materials in the prior art are solved, and high wear resistance and long-term self-lubricating properties of the sliding bed plate are achieved.

CN119839284APending Publication Date: 2025-04-18CRSC RESEARCH & DESIGN INSTITUTE GROUP CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510002204.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-02
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

In the preparation of copper-based graphite self-lubricating composite materials, the existing problems of low energy conversion rate, cladding defects, low interface bonding strength between copper and graphite, degraded mechanical properties of the material, and easy decomposition of solid lubricating materials at high temperatures, resulting in the inability to effectively guarantee the wear resistance and self-lubricity of the sliding bed plate.

Method used

Copper-based wear-resistant self-lubricating composite powder is adopted, including main metal powder (Cu powder), reinforced metal powder (Sn, Fe, Ni, etc.), coated wear-resistant material powder (such as SiC, TiC, etc.) and coated solid lubricating material powder (such as graphite, WS2, etc.), and laser cladding technology is used to form a wear-resistant self-lubricating cladding layer on the surface of the sliding bed board, and stress removal, vacuum sealing and surface processing are carried out to improve the comprehensive mechanical properties and self-lubricity of the cladding layer.

Benefits of technology

The sliding bed plate surface has achieved a high-quality wear-resistant self-lubricating cladding, which has good wear resistance, friction reduction and long-term self-lubricating properties, high bond strength and good consistency, convenient construction, high preparation efficiency and low cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119839284A_ABST
    Figure CN119839284A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of surface strengthening, and particularly relates to wear-resistant self-lubricating composite powder for a slide plate, a cladding layer and a preparation method of the cladding layer. The composite powder comprises a main body metal component, a reinforced metal component, a coated wear-resistant material component and a lubricating material component, and can be used for preparing a wear-resistant self-lubricating cladding layer on the surface of the slide plate, and the preparation method comprises the following steps: (1) preparing the copper-based wear-resistant self-lubricating composite powder; (2) pretreatment of a slide plate cladding area; (3) preparing a surface metallurgy strengthening cladding layer; and (4) carrying out destressing treatment, vacuum hole sealing and surface processing treatment on the cladding layer. The prepared cladding layer material is suitable for complex working conditions of rail transit, meets the requirements for large alternating stress and friction load, can effectively improve the wear resistance and self-lubricating performance of a slide plate base body, obviously improves the using effect and prolongs the service life of the slide plate base body, and has the advantages of being convenient to construct, high in preparation efficiency, low in cost and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of surface strengthening, and in particular relates to a wear-resistant self-lubricating composite powder of a slide bed plate, a cladding layer and a preparation method thereof. Background Art

[0002] The slide bed is an important part of the turnout. Its function is to support the point rail and the base rail, and to ensure that the point rail can slide normally on the platform. The slide bed of the railway turnout, which is made of carbon steel or low alloy steel with hard chrome electroplating on the surface, needs to be regularly oiled and maintained by manual maintenance to ensure lubrication and avoid wear. These operations not only waste a lot of manpower and material resources, but also increase construction risks. At the same time, the slide bed is not easy to retain lubricating oil. Excessive loss of lubricating oil will cause serious pollution to the surrounding environment and accelerate the corrosion of the rubber pad. Solid lubricating materials have the characteristics of friction reduction, anti-wear and self-lubricating. The application of this technology is one of the effective ways to solve the above problems.

[0003] In terms of solid lubricating materials and technologies, related solid self-lubricating material research directions include: metal-based solid composite self-lubricating materials (mainly Fe, Ni, Cu alloys), ceramic-based solid self-lubricating materials, and polymer-based solid self-lubricating materials. Among them, metal-based solid composite self-lubricating materials can best meet the performance requirements of railway equipment slide bed plates. At present, the technical routes are mainly based on the preparation of blocks and coatings. Block materials require sintering processes such as powder metallurgy, which have high costs, complex preparation processes, difficulties in welding heterogeneous materials, and poor application matching. Therefore, the use of laser cladding to prepare protective coatings is the preferred option.

[0004] Compared with iron-based and nickel-based solid composite self-lubricating materials, copper-based graphite self-lubricating composite materials have the advantages of good toughness, plasticity and corrosion resistance of metals, and at the same time have the self-lubricating properties of graphite, and the preparation cost is low, which has attracted widespread attention in the industry. When frictionally matched with steel materials, graphite can form a lubricating film to reduce friction, and the copper matrix can effectively support the lubricating film. However, the existing technology mainly has the following problems:

[0005] (1) Due to the high thermal conductivity and high reflectivity of copper, its surface absorbs insufficient laser energy, resulting in low energy conversion rate and cladding defects. Therefore, it is difficult to achieve high-quality preparation of copper-based materials with traditional laser processing technology. Patent CN09807331A proposes to use powder metallurgy to directly form and prepare the entire slide bed plate. Although it has good wear resistance, it has problems such as high cost, complex welding of heterogeneous materials, and poor application matching. Patent CN 116162927A proposes a preparation method of prefabricated precursor sheets combined with two laser claddings. Although it solves the problem of low laser energy absorption rate, the preparation process is complicated and prone to local stratification problems, and the cladding quality cannot be effectively guaranteed.

[0006] (2) Copper and graphite have poor wettability, and the interface bonding strength between the two is low. Graphite forms a mesh structure that splits the matrix, and is prone to potential defects such as pores and cracks, resulting in a decrease in the mechanical properties of the matrix material. Under high pressure and friction, the two have poor collaborative deformation capabilities, and large-area graphite cracking and peeling problems cause serious wear of the slide bed, and the self-lubricating properties cannot be effectively guaranteed; the surface roughness and friction coefficient of the material increase and fluctuate, making it more difficult for the pointed rail friction pair to slide and aggravating wear, and in severe cases even causing the slide bed to be scrapped;

[0007] (3) The added solid lubricant is easily decomposed by high temperature energy during the laser cladding process. Some elements are directly vaporized or oxidized to form gases. These gases will cause defects such as three-dimensional microcracks and pore channels in the cladding matrix, affecting its overall strength and density, resulting in a decrease in its wear resistance and resistance to alternating impact loads. Summary of the invention

[0008] In view of the above problems, the present invention provides a wear-resistant self-lubricating composite powder for a slide bed, a cladding layer and a preparation method thereof. The cladding layer material prepared by the present invention is suitable for complex working conditions of rail transit, meets the requirements of large alternating stress and friction load, has good wear resistance and friction reduction and long-term self-lubrication, and has high comprehensive mechanical properties such as bonding strength of the cladding layer, good consistency, and has the advantages of convenient construction, high preparation efficiency, and low cost.

[0009] In a first aspect, the present invention provides a composite powder for preparing a wear-resistant self-lubricating cladding layer on the surface of a slide bed plate, comprising: i) a main metal powder with a particle size of 45 to 100 μm; ii) a reinforcing metal powder with a particle size of 45 to 100 μm; iii) a coated wear-resistant material powder with a particle size of ≤35 μm; and, iv) a coated solid lubricating material powder with a particle size of ≤45 μm;

[0010] Among them, the main metal powder is Cu powder; the strengthening metal powder is selected from one or more of Sn powder, Fe powder, Ni powder, Co powder, Cr powder, Mn powder or Ag powder; the aforementioned coating refers to the surface coating of a double-layer shell of metal tin and metal copper or the surface coating of a single-layer shell of copper-tin alloy; the mass ratio of the main metal powder, the strengthening metal powder, the coated wear-resistant material powder and the coated solid lubricating material powder is 50~90:5~20:1~10:4~20.

[0011] Cu powder is the main material, which plays an integral supporting role in the cladding layer. Its elastic modulus, toughness, plasticity and lubricity are better than those of the carbon steel material of the slide bed substrate, so as to improve its resistance to impact loads and friction reduction performance. The powder particles are spherical in shape. On the basis of the main material, one or more other metal elements with a certain solid solubility are added to strengthen copper. Specifically, the lattice distortion strengthening effect caused by solid solution reduces its laser reflectivity, improves the direct absorption rate of laser energy of the copper substrate, and improves the comprehensive mechanical properties and wear and corrosion resistance of the substrate.

[0012] The wear-resistant material powder makes the cladding layer have a certain hardness, and can form a multi-particle friction film pinning support point on a microscopic scale to stabilize the pinned friction film, avoid its rapid metabolic loss and reduce the wear depth, ensure the stability of friction and friction coefficient during sliding, and also prevent adhesion and reduce noise. One or more wear-resistant materials such as carbides, nitrides, oxides, etc. with high hardness can be selected. In some embodiments, the wear-resistant material is selected from Cr3C2, SiC, TiC, BN, TiN, ZrN, Al2O3, SiO2, TiO2, ZrO2 or high / medium carbon ferrochrome (high carbon ferrochrome is ferrochrome with a carbon content of 4 to 8 wt%, and medium carbon ferrochrome is ferrochrome with a carbon content of 0.5 to 4 wt%) or a combination of more than two. In some embodiments, the core particles of the wear-resistant material powder are nanometer-scale, which can ensure good stability and service performance of the friction film.

[0013] The solid lubricant powder is embedded in the matrix to play a self-lubricating role, ensuring the laminar isolation of the friction attachment and the stable metabolism of the friction film. One or more of the laminar solid lubricant or the tough-to-brittle transition lubricant can be selected. In some embodiments, the solid lubricant is selected from one or a combination of two or more of graphite (including spherical graphite, flake graphite, graphite fiber, graphene and carbon nanotubes, etc.), WS2, MoS2, h-BN or CaF2.

[0014] In order to further improve the bonding strength between the wear-resistant material powder and the solid lubricant material powder and the substrate respectively, and avoid their decomposition or oxidation caused by the high temperature during the cladding process, the above-mentioned wear-resistant material powder and solid lubricant material powder are subjected to a copper-tin double-layer shell surface coating treatment or a copper-tin alloy single-layer shell surface coating treatment, that is, the whole has a core-shell structure, with the wear-resistant material or solid lubricant material as the core and the coating material as the shell, and from the core to the shell, there are wear-resistant material / solid lubricant material, a first coating layer of metal copper and a second coating layer of metal tin in sequence; or, from the core to the shell, there are wear-resistant material / solid lubricant material, a copper-tin alloy coating in sequence.

[0015] In some embodiments, the mass ratio of copper to tin in the surface coating is 50-99:1-50, and the average thickness of the coating layer of the wear-resistant material powder and the solid lubricant material powder is not less than 4 μm. The surface coating methods of powder particles such as chemical plating, solid phase reaction, liquid phase ion precipitation, mechanochemical, and vapor deposition can be used. The surface copper and the matrix copper have good homogeneous wettability and high melting point, and are not easily affected by the high temperature energy of the laser to melt rapidly, causing premature exposure of the second phase additive; tin has a lower melting point and better low-temperature affinity with copper than nickel. After melting, tin can promote the melting and bonding of the surface copper of the solid lubricant powder and the matrix copper, reduce intergranular defects, and improve the comprehensive mechanical properties of the cladding layer.

[0016] The mass ratio of main metal powder, reinforced metal powder, coated wear-resistant material powder and coated solid lubricant powder is limited to 50-90:5-20:1-10:4-20 because too high content of main metal powder and reinforced metal powder will lead to a sharp decrease in the laser energy absorption rate of the cladding layer, resulting in energy waste and cost increase; too low content will lead to a sudden change in the main performance, and its ability to resist impact loads and reduce friction will be affected. Too high content of coated wear-resistant material powder will lead to too high hardness of the cladding layer, too many pore crack defects formed by the decomposition of compound materials, reduced comprehensive mechanical properties of the cladding layer, and reduced matching with the friction and wear of the point rail to cause eccentric wear problems; too low content will fail to stably pin the friction film, resulting in a decrease in wear resistance. Too high content of coated solid lubricant powder will lead to a decrease in density and comprehensive mechanical properties, while too low content will affect the stable formation and metabolism of the friction film and fail to play a stable self-lubricating role.

[0017] In a second aspect, the present invention provides a use of the aforementioned composite powder in preparing a wear-resistant self-lubricating cladding layer on the surface of a slide bed plate.

[0018] In a third aspect, the present invention provides a slide plate, including a slide plate substrate, the surface of which is combined with a wear-resistant self-lubricating cladding layer, wherein the wear-resistant self-lubricating cladding layer is formed by depositing the aforementioned composite powder on the surface of the slide plate substrate through laser cladding.

[0019] In a fourth aspect, the present invention provides a method for preparing a wear-resistant self-lubricating cladding layer on the surface of a slide bed plate, comprising: (1) preparing a copper-based wear-resistant self-lubricating composite powder: uniformly mixing the components of the aforementioned composite powder; (2) pretreatment of the slide bed plate cladding area: preheating the slide bed plate cladding area after surface treatment; (3) preparing a surface metallurgical strengthening cladding layer: using a laser cladding method, depositing the uniformly mixed composite powder on the preheated slide bed plate surface to form a cladding layer; (4) stress relief treatment, vacuum sealing and surface processing of the cladding layer to obtain a wear-resistant self-lubricating cladding layer on the slide bed plate surface.

[0020] In some embodiments, the composite powder is mixed uniformly in a certain proportion by a double motion mixing method. The barrel speed is 10-40r / min, the blade speed is 40-100r / min, and the mixing time is not less than 2h. Before mixing, the main metal powder and the reinforcing metal powder are broken up into agglomerated particles by an air flow crusher, and the large particles that do not meet the particle size requirements are screened out by a 90-150 mesh vibrating screen to ensure the overall uniformity of the powder; and in order to increase the fluidity of the powder, the main metal powder and the reinforcing metal powder are preferably spherical particles.

[0021] In some implementation schemes, after the surface of the slide plate is sandblasted, it is repeatedly cleaned with a metal cleaning agent until there is no rust, oil or other impurities on the surface, and then dried for use. The impeller surface cleanliness reaches Sa2.5 or above, and the roughness reaches Ra3.2 or above, which is beneficial to increase the contact area and reduce interface impurities, and improve the bonding strength between the cladding layer and the substrate. The sandblasting is zircon sand, brown corundum, quartz sand, corundum, etc., with a mesh range of 20 to 80 meshes. Preheat the surface of the slide plate to no more than 200°C to avoid thermal stress cracks and local overheating deformation.

[0022] In some embodiments, a CO2 high-energy laser device is used in the laser cladding process, with a laser power of 1 to 15KW, a spot size of 0.1 to 3.0 mm, a scanning rate of 0.1 to 5 m / min, an overlap rate of 40 to 80%, a powder feeding speed of 10 to 200 g / min, and a cladding single layer thickness of 0.1 to 2.0 mm. The protective gas used in the laser cladding process is an inert gas such as argon and helium, and a single-layer or multi-layer superimposed cladding method can be selected.

[0023] In some embodiments, after laser cladding to the required thickness is completed, the cladding layer is subjected to stress removal, vacuum sealing and surface processing. After the powder is solidified at high temperature to form a surface cladding layer, there will be large residual stress, which can easily cause it to crack and fall off. The surface of the cladding layer can be treated with heat sources such as flame, laser, and electron beam to eliminate residual stress and ensure that the parts have no thermal deformation. The heat treatment temperature is 100-450°C and the heat treatment time is 10-120 minutes.

[0024] In some embodiments, the high energy of the high-energy laser may cause a small amount of coated wear-resistant material powder or coated solid lubricant powder to decompose, resulting in defects such as microcracks and pore channels, affecting the density and organizational strength of the cladding layer. Therefore, the present invention adopts a vacuum melting polytetrafluoroethylene (PTFE) sealing method for closed-cell treatment. Polytetrafluoroethylene is heated to 320-360°C to make it completely molten, and the sliding bed plate cladding layer area is immersed in the molten pool and pumped to a vacuum negative pressure for 5-20 minutes to ensure that all the pore channels of the cladding layer are completely filled, and then taken out for natural cooling or drying to solidify quickly. Polytetrafluoroethylene material has excellent characteristics such as high temperature stability, chemical corrosion resistance, high insulation, low friction coefficient, and good sealing. The vacuum melting sealing treatment not only reduces the potential crack source, but also blocks the entry of corrosive foreign matter such as acid, alkali, and dust into the channel, improves the overall strength of the cladding layer, and effectively reduces its friction coefficient. In particular, the friction coefficient between polytetrafluoroethylene and steel is extremely low (0.02-0.1). After sealing with polytetrafluoroethylene (PTFE), the friction coefficient and wettability of the cladding layer are significantly reduced, thereby improving the wear resistance and self-lubrication of the slide bed. In addition, as the friction of the cladding layer is lost during use, new polytetrafluoroethylene in the closed channel will be continuously replenished and exposed to the friction pair surface, further ensuring the self-lubrication of the cladding layer throughout its service life, which significantly improves the use effect and service life of the slide bed. After the cladding layer cools to room temperature, surface machining is performed, and flat grinding is performed to meet the requirements of size and roughness.

[0025] The beneficial effects of the present invention are:

[0026] 1. The composite powder provided by the present invention includes main metal powder, strengthening metal powder, coated wear-resistant material powder and coated solid lubricant material powder. The main metal powder copper powder is the main material, which can form a cladding layer matrix with good resistance to impact loads and friction reduction performance; the strengthening metal powder as a strengthening material effectively improves the energy absorption rate of the metal copper main material and plays a role in solid solution strengthening; the coated wear-resistant material powder and the coated solid lubricant material powder ensure the stable formation and orderly metabolism of the friction film, effectively reduce the friction wear of the friction pair, and significantly improve the wear resistance and self-lubrication of the slide bed. The mutual coupling of the four components not only ensures the excellent performance of the protective cladding layer, but also effectively improves the process feasibility and preparation efficiency.

[0027] 2. The composite powder provided by the present invention is specially added with coated wear-resistant material powder and solid lubricant material powder. After the copper-tin double-layer coating treatment, the surface copper and the base copper have good homogeneous wettability, and the high melting point is not easily affected by the high-temperature energy of the laser to melt rapidly, causing the second phase additive to be exposed prematurely; the melting point of tin is lower, and the low-temperature affinity with copper is better than nickel. After tin is melted, it can promote the melting and bonding of the surface copper of the solid lubricant material and the base copper, reduce intercrystalline defects, and improve the comprehensive mechanical properties of the cladding layer. And after cooling and solidification, a buffer bonding layer is formed between the main copper and the heterogeneous particles, which can significantly improve the shortcomings of mechanical bonding and poor wettability between the two, improve the interface bonding strength, effectively reduce the problem of excessive wear and peeling of heterogeneous lubricating particles during friction, and ensure the stable performance of its self-lubricating performance.

[0028] 3. The preparation method of the wear-resistant self-lubricating slide bed provided by the present invention is to achieve the basic requirements of the surface of the cladding layer through stress relief heat treatment and surface flat grinding; and to fill the three-dimensional microcracks and pore channel defects formed by the decomposition of a small amount of compounds through the vacuum melting polytetrafluoroethylene sealing method. Compared with the impregnation of water-based polytetrafluoroethylene dispersion under normal pressure, the vacuum replacement of the internal gas in this method is more complete, the pore filling effect is better, and the preparation efficiency is higher. After the above treatment, the new polytetrafluoroethylene in the closed channel will be continuously replenished and exposed to the surface of the friction pair during use, so that the self-lubricating effect is enhanced and exists for a long time. Therefore, while ensuring the overall strength and density of the cladding layer, combined with the advantage of the ultra-low friction coefficient between polytetrafluoroethylene and steel, the effect of continuously replenishing the self-lubricating characteristics during the service life of the slide bed plate is achieved. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 The preparation process of the wear-resistant self-lubricating cladding layer of Example 1;

[0030] Figure 2 This is a longitudinal electron microscope photograph (50×) of the wear-resistant self-lubricating cladding layer of Example 1;

[0031] Figure 3 This is an electron microscope photograph (100×) of the surface of the wear-resistant self-lubricating cladding layer of Example 1 after flat grinding. DETAILED DESCRIPTION

[0032] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention is clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0033] In the following examples, component C and component D are prepared by conventional powder particle surface coating method, the mass ratio of copper to tin in the coating material is 50-99:1-50, and the average thickness of the surface coating of component C and component D is not less than 4 μm.

[0034] Example 1 Copper-based SiC / graphite wear-resistant self-lubricating cladding layer on the surface of the slide plate

[0035] Preparation process Figure 1 As shown, the details are as follows:

[0036] Step 1: Preparation of copper-based wear-resistant self-lubricating composite powder. Component A is pure Cu powder with a particle size range of 50-80μm; component B is a mixed powder of Fe and Ni in equal molar proportions with a particle size range of 50-80μm; component C is a copper-tin double-layer coated SiC powder with a particle size range of 15-25μm; component D is a copper-tin double-layer coated graphite powder with a particle size range of 15-40μm. Components A and B are broken up into agglomerated particles by an air flow crusher, and large particles are screened out by 90 and 150 mesh vibrating screens. The mass fraction ratio of components A, B, C, and D in the composite powder raw materials is 70%: 15%: 5%: 10%, and components A, B, C, and D are mixed evenly by a double motion mixing method. The barrel speed is 30r / min, the blade speed is 80r / min, and the mixing time is 3h.

[0037] Step 2: Pretreatment of the slide plate cladding area. The slide plate surface is sandblasted with 60-mesh quartz sand, and then repeatedly cleaned with acetone metal cleaning agent until there is no rust, oil or other impurities on the surface, and dried for use. The slide plate surface cleanliness is Sa2.5 and the roughness is Ra6.3. The slide plate surface is preheated to 150°C.

[0038] Step 3: Preparation of surface metallurgical strengthening cladding layer. In the preheated slide plate surface area, the composite powder is rapidly melted and solidified by high-energy laser irradiation to form a cladding layer. The main process parameters of laser cladding are: CO2 high-energy laser, laser power 3KW, spot size Φ2.0mm, scanning rate 0.5m / min, overlap rate 60%, powder feeding speed 100g / min, single-pass cladding thickness of about 1mm, total cladding layer thickness of 4mm, argon protection, and laser cladding layer, such as Figure 2 As shown, it can be seen that the prepared laser cladding layer has good quality and no large-area macroscopic defects.

[0039] Step 4: stress relief treatment, vacuum sealing and surface processing of the cladding layer. The surface of the cladding layer is flame heated to 200°C and heat treated for 90 minutes. The polytetrafluoroethylene is heated to 350°C to make it completely molten, and then the cladding layer area of ​​the slide plate is immersed in the molten pool and evacuated to a vacuum negative pressure. After immersion for 10 minutes, it is taken out and naturally cooled until it is completely solidified. Finally, it is processed with a surface grinder to a roughness of Ra3.2 to obtain a copper-based SiC / graphite wear-resistant self-lubricating cladding layer on the surface of the slide plate. Figure 3 As shown, it can be seen that the surface is smooth and complete, the overall strength and consistency are good, there is no slag falling, pitting and other problems, and it has good processing performance.

[0040] Example 2 Copper-based Al2O3 / WS2 wear-resistant self-lubricating cladding layer on the surface of the slide plate

[0041] The preparation method is as follows:

[0042] Step 1: Preparation of copper-based wear-resistant self-lubricating composite powder. Component A is pure Cu powder with a particle size range of 60-90μm; component B is a mixed powder of Fe, Ni, and Co in equal molar proportions with a particle size range of 60-90μm; component C is a copper-tin double-layer coated Al2O3 powder with a particle size range of 10-20μm; component D is a copper-tin double-layer coated WS2 powder with a particle size range of 20-40μm. Components A and B are broken up into agglomerated particles by an air flow crusher, and large particles are screened out by 90 and 150 mesh vibrating screens. The mass fraction ratio of components A, B, C, and D in the composite powder raw materials is 60%: 20%: 5%: 15%, and components A, B, C, and D are mixed evenly by double motion mixing. The barrel speed is 20r / min, the blade speed is 60r / min, and the mixing time is 4h.

[0043] Step 2: Pretreatment of the slide plate cladding area. The slide plate surface is sandblasted with 40 mesh zircon sand, and then repeatedly cleaned with acetone metal cleaning agent until there is no rust, oil or other impurities on the surface, and dried for use. The slide plate surface cleanliness is Sa3.0, and the roughness is Ra6.3. The slide plate surface is preheated to 200℃.

[0044] Step 3: Preparation of surface metallurgical strengthening cladding layer. In the preheated slide plate surface area, the composite powder is rapidly melted and solidified by high-energy laser irradiation to form a cladding layer. The main process parameters of laser cladding are: CO2 high-energy laser, laser power 5KW, spot size Φ1.5mm, scanning rate 2.0m / min, overlap rate 80%, powder feeding speed 200g / min, single-pass cladding thickness of about 1.5mm, total cladding layer thickness of 6mm, argon protection, and laser cladding layer.

[0045] Step 4: stress relief treatment, vacuum sealing and surface processing of the cladding layer. The surface of the cladding layer is flame heated to 250°C and heat treated for 60 minutes. The polytetrafluoroethylene is heated to 340°C to make it completely molten, and then the cladding area of ​​the slide bed is immersed in the molten pool and evacuated to vacuum negative pressure. After immersion for 15 minutes, it is taken out and naturally cooled until it is completely solidified. Finally, the surface is processed by a flat grinder to a roughness of Ra3.2 to obtain a copper-based Al2O3 / WS2 wear-resistant self-lubricating cladding layer on the surface of the slide bed.

[0046] Example 3: Copper-based ZrO2 / h-BN wear-resistant self-lubricating cladding layer on the surface of the slide plate

[0047] The preparation method is as follows:

[0048] Step 1: Preparation of copper-based wear-resistant self-lubricating composite powder. Component A is pure Cu powder with a particle size range of 60-90μm; component B is a mixed powder of Fe, Ni, Co, Cr, Sn in a molar ratio of 1:1:1:1:0.1, with a particle size range of 50-80μm; component C is a copper-tin double-layer coated ZrO2 powder with a particle size range of 10-30μm; component D is a copper-tin double-layer coated h-BN powder with a particle size range of 10-30μm. Components A and B are broken up into agglomerated particles by an air flow crusher, and large particles are screened out by 90 and 150 mesh vibrating screens. The mass fraction ratio of components A, B, C, and D in the composite powder raw materials is 55%: 15%: 10%: 20%, and components A, B, C, and D are mixed evenly by double motion mixing. The barrel speed is 40r / min, the blade speed is 90r / min, and the mixing time is 1.5h.

[0049] Step 2: Pretreatment of the cladding area of ​​the slide bed. The slide bed surface is sandblasted with 60-mesh brown corundum, and then repeatedly cleaned with acetone metal cleaning agent until there is no rust, oil or other impurities on the surface, and dried for use. The slide bed surface cleanliness is Sa2.5 and the roughness is Ra6.3. The slide bed surface is preheated to 180℃.

[0050] Step 3: Preparation of surface metallurgical strengthening cladding layer. In the preheated slide plate surface area, the composite powder is rapidly melted and solidified by high-energy laser irradiation to form a cladding layer. The main process parameters of laser cladding are: CO2 high-energy laser, laser power 7KW, spot size Φ1mm, scanning rate 3m / min, overlap rate 60%, powder feeding speed 150g / min, single-pass cladding thickness of about 2mm, total cladding layer thickness of 8mm, argon protection, and laser cladding layer.

[0051] Step 4: Stress relief treatment, vacuum sealing and surface processing of the cladding layer. The surface of the cladding layer is laser heated to 300°C and heat treated for 45 minutes. The polytetrafluoroethylene is heated to 360°C to make it completely molten, and then the cladding area of ​​the slide bed is immersed in the molten pool and evacuated to vacuum negative pressure. After immersion for 10 minutes, it is taken out and naturally cooled until it is completely solidified. Finally, the surface is processed by a flat grinder to a roughness of Ra3.2 to obtain a copper-based ZrO2 / h-BN wear-resistant self-lubricating cladding layer on the surface of the slide bed.

[0052] Example 4: Copper-based ZrO2-SiO2 / WS2 wear-resistant self-lubricating cladding layer on the surface of the slide plate

[0053] The preparation method is as follows:

[0054] Step 1: Preparation of copper-based wear-resistant self-lubricating composite powder. Component A is pure Cu powder with a particle size range of 70-100 μm; component B is a mixed powder of Fe, Ni, and Co in equal molar proportions with a particle size range of 60-90 μm; component C is a copper-tin alloy single-layer coated ZrO2 and SiO2 particle mixed powder, the copper-tin alloy mass ratio is 95%:5%, and the powder particle size range is 10-20 μm; component D is a copper-tin double-layer coated WS2 powder with a particle size range of 20-40 μm. Components A and B are broken up into agglomerated particles by an air flow crusher, and large particles are screened out by 90 and 150 mesh vibrating screens. The mass fraction ratio of components A, B, C, and D in the composite powder raw material is 80%:8%:5%:7%. The other steps and process parameters are the same as those in Example 2, and a copper-based ZrO2-SiO2 / WS2 wear-resistant self-lubricating cladding layer on the surface of the slide bed is obtained.

[0055] Comparative Example 1: Copper / graphite wear-resistant self-lubricating cladding layer on the surface of the slide plate

[0056] The raw materials for preparing the cladding layer consist only of component A and component D, wherein component A is pure Cu powder with a particle size range of 50 to 80 μm; component D is pure graphite powder with a particle size range of 15 to 40 μm. The mass fraction ratio of component A to component D in the powder raw materials is 90%:10%. Except that vacuum PTFE sealing is not performed, the other preparation steps and preparation parameters of the cladding layer are the same as those in Example 1.

[0057] Comparative Example 2: Wear-resistant self-lubricating copper / nickel-coated graphite cladding layer on the surface of the slide plate

[0058] The raw materials for preparing the cladding layer consist only of component A and component D, wherein component A is pure Cu powder with a particle size range of 50 to 80 μm; component D is nickel-coated pure graphite powder with a particle size range of 15 to 40 μm. The mass fraction ratio of component A to component D in the powder raw materials is 90%:10%. Except that vacuum PTFE sealing is not performed, the other preparation steps and preparation parameters of the cladding layer are the same as those in Example 1.

[0059] Comparative Example 3: Wear-resistant self-lubricating copper / nickel-coated graphite cladding layer on the surface of the slide plate

[0060] The raw materials for preparing the cladding layer consist only of component A and component D, wherein component A is pure Cu powder with a particle size range of 50 to 80 μm; component D is nickel-coated pure graphite powder with a particle size range of 15 to 40 μm. The mass fraction ratio of component A to component D in the powder raw materials is 90%:10%. The preparation steps and preparation parameters of the cladding layer are the same as those in Example 1.

[0061] Comparative Example 4: Copper-based SiC / graphite wear-resistant self-lubricating cladding layer on the surface of the slide plate

[0062] Except for using a water-based polytetrafluoroethylene dispersion with a solid content of 30% for impregnation and sealing, other contents are the same as those in Example 1.

[0063] The Vickers hardness was measured using a HVS-1000Z Vickers hardness tester, with a load of 4.9N and a dwell time of 10 seconds. The hardness report was the average of 5 measured values. The friction coefficient and reference "GB / T 43853-2024 Laser repair layer high temperature friction and wear performance test ball-disc method" were tested under room temperature conditions. The performance test results are shown in Table 1.

[0064] Table 1

[0065]

[0066]

[0067] The test results show that compared with the preparation methods of Comparative Examples 1 to 4, the slide bed surface cladding layer prepared in the embodiment of the present invention has significantly higher hardness, lower average friction coefficient and specific wear rate, indicating that the cladding layer of the present invention has better wear resistance and self-lubricating properties and excellent comprehensive mechanical properties.

[0068] The preferred embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.

Claims

1. A composite powder for preparing a wear-resistant self-lubricating cladding layer on the surface of a slide bed, characterized in that: The composite powder comprises: i) a main metal powder having a particle size of 45 to 100 μm; ii) reinforced metal powder with a particle size of 45 to 100 μm; iii) coated wear-resistant material powder with a particle size of ≤35 μm; and, iv) Coated solid lubricant powder with a particle size of ≤45 μm; The main metal powder is Cu powder; the strengthening metal powder is selected from one or a combination of two or more of Sn powder, Fe powder, Ni powder, Co powder, Cr powder, Mn powder or Ag powder; the coating is a double-layer shell surface coating of metal tin and metal copper or a single-layer shell surface coating of copper-tin alloy; the mass ratio of the main metal powder, the strengthening metal powder, the coated wear-resistant material powder and the coated solid lubricating material powder is 50-90:5-20:1-10:4-20.

2. The composite powder according to claim 1, characterized in that The mass ratio of copper to tin in the surface coating is 50-99:1-50, and the average thickness of the surface coating of the wear-resistant material powder and the solid lubricating material powder is not less than 4 μm respectively.

3. The composite powder according to claim 1, characterized in that The wear-resistant material is selected from one or a combination of two or more of Cr3C2, SiC, TiC, BN, TiN, ZrN, Al2O3, SiO2, TiO2, ZrO2 or ferrochrome containing 0.5 to 8 wt% carbon.

4. The composite powder according to claim 1, characterized in that The solid lubricating material is selected from one or a combination of two or more of graphite, WS2, MoS2, h-BN or CaF2.

5. Use of the composite powder according to any one of claims 1 to 4 in preparing a wear-resistant self-lubricating cladding layer on the surface of a slide bed.

6. A slide bed plate, comprising a slide bed plate substrate, wherein the surface of the slide bed plate substrate is combined with a wear-resistant self-lubricating cladding layer, characterized in that: The wear-resistant self-lubricating cladding layer is formed by depositing the composite powder according to any one of claims 1 to 4 on the surface of the slider bed substrate through laser cladding.

7. A method for preparing a wear-resistant self-lubricating cladding layer on the surface of a slide bed, characterized in that: The preparation method comprises: (1) Preparation of copper-based wear-resistant self-lubricating composite powder: uniformly mixing the components of the composite powder according to any one of claims 1 to 4; (2) Pretreatment of the slide plate cladding area: preheat the slide plate cladding area after surface treatment; (3) Preparation of surface metallurgical strengthening cladding layer: using laser cladding method, a uniformly mixed composite powder is deposited on the surface of the cladding area of ​​the preheated slide bed plate to form a cladding layer; (4) The cladding layer is subjected to stress relief treatment, vacuum sealing and surface processing to obtain a wear-resistant and self-lubricating cladding layer on the surface of the slide bed.

8. The preparation method according to claim 7, characterized in that: The parameters of the laser cladding include: being carried out under the protection of inert gas, laser power of 1-15KW, spot size of 0.1-3.0mm, scanning rate of 0.1-5m / min, overlap rate of 40-80%, powder feeding speed of 10-200g / min, and cladding single layer thickness of 0.1-2.0mm.

9. The preparation method according to claim 7, characterized in that: The cladding layer is subjected to heat treatment to relieve stress, wherein the heat treatment temperature is 100 to 450° C. and the time is 10 to 120 minutes.

10. The preparation method according to claim 7, characterized in that: The vacuum sealing comprises: immersing the heat-treated cladding layer in vacuum-melted polytetrafluoroethylene for 5 to 20 minutes.

Citation Information

Cited By

  • Antifriction and wear-resistant coating material as well as preparation method and application thereof

    CN121272403A